Costs in inflammatory bowel diseases - Petryszyn, Paweł W.; Witczak, Izabela (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Variables influencing total direct medical costs in inflammatory bowel diseases include country, diagnosis (generally, patients with Crohn’s disease generated higher costs compared with patients with ulcerative colitis), and year since diagnosis. In all studies the mean costs were higher than the median costs, which indicates that a relatively small group of the most severely ill patients significantly affect the total cost of treatment of these diseases. A major component of direct medical costs was attributed to hospitalisation, ranging from 49% to 80% of the total. The costs of surgery constituted 40–61% of inpatient costs. Indirect costs in inflammatory bowel diseases, unappreciated and often underestimated (considered by few authors and as a loss of work), are in fact important and may even exceed direct medical costs.